Method for preparing iridescent cuprous oxide nanoparticle photonic crystal
By controlling the crystal form of cuprous oxide nanoparticles and using high molecular weight polymers, the self-assembly of cuprous oxide nanoparticles into three-dimensional ordered photonic crystals is achieved, solving the problem that structural colors in the prior art do not have iridescent colors, and achieving brilliant iridescent colors and high fastness structural colors.
Patent Information
- Application Number
- CN202411704105.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-26
AI Technical Summary
It is difficult for the prior art to form photonic crystals with three-dimensional ordered structures through cuprous oxide nanoparticles, resulting in the structural color not having iridescent color.
By controlling the crystal form of cuprous oxide nanoparticles, polycrystalline monodispersed spherical nanoparticles are synthesized using high molecular weight polyvinylpyrrolidone and polyethylene glycol to self-assemble them into three-dimensional ordered photonic crystals.
The copper oxide nanoparticles are self-assembled into photonic crystals with three-dimensional ordered structures, producing gorgeous iridescent colors, and improving the fastness of the structural color through adhesives.
Smart Images

Figure CN119528203A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photonic crystal preparation, and specifically relates to a method for preparing cuprous oxide nanoparticle photonic crystals with iridescent colors, wherein the photonic crystals are prepared by self-assembly of high-refractive-index nanoparticles, and structural colors with iridescent colors are obtained by controlling the particle crystal form. Background Art
[0002] Structural color is produced by scattering, interference or diffraction of visible light when it is incident on an object with a spatial period similar to the wavelength. Compared with pigment color, structural color has the characteristics of no fading, easy color control and brilliant color. Photonic crystal is a material with periodic changes in dielectric constant and refractive index. It produces iridescent structural color through the diffraction of visible light in its structure, and has very good application prospects in the field of textile printing and dyeing.
[0003] In order to improve the structural color fastness on the textile substrate, it is generally necessary to use an adhesive to bond the structural elements in the photonic crystal, such as nanospheres, together, and then bond them to the textile substrate. However, the coloring of conventional photonic crystal structures on textile substrates tends to use polymers and inorganic substances with low refractive index (refractive index n is 1.4-1.5). When the adhesive is added, although the structural color fastness is improved, because it is very close to the refractive index of the structural element in the crystal structure, the refractive index contrast becomes very small, resulting in a significant decrease in the diffraction intensity, thereby making the color worse (Light: Science & Applications, 2022, 11, 316).
[0004] In order to obtain strong and gorgeous iridescent colors on textile substrates, it is necessary to use structural elements with high refractive index (n>2.0) to form photonic crystals. Due to its advantages such as high refractive index (n is 2.7), simple synthesis and low price, cuprous oxide is regarded as a very promising substance for preparing photonic crystals. The literature does use cuprous oxide nanoparticles as structural elements to construct structural colors (CN109850932B; Nanoscale, 2020, 12, 3220; ACS Appl. Mater. Interfaces 2021, 13, 57796). However, studies have shown that because these cuprous oxide nanoparticles are single crystals, the interfacial tension cannot make them completely spherical, so they cannot be densely stacked into photonic crystals with three-dimensional ordered structures.
[0005] So far, the structural color of cuprous oxide nanoparticles is believed to be generated based on Mie scattering of a single nanoparticle (Advanced Materials 2015, 27, 7432). Therefore, this structural color does not have the iridescence unique to photonic crystals. Based on this, how to make cuprous oxide nanoparticles form photonic crystals to obtain brilliant iridescence is a technical problem to be solved. Summary of the invention
[0006] In view of the shortcomings of the above background technology, the purpose of the present invention is to provide a method for preparing cuprous oxide nanoparticle photonic crystals with iridescent colors, which obtains monodisperse spherical particles by controlling the crystal form of cuprous oxide nanoparticles, so that they can self-assemble into a three-dimensional ordered photonic crystal structure, thereby producing gorgeous iridescent colors.
[0007] To solve the above technical problems, the purpose of the present invention is achieved as follows:
[0008] A method for preparing iridescent cuprous oxide nanoparticle photonic crystals, wherein the structural unit is a polycrystalline monodisperse spherical cuprous oxide nanoparticle, which is synthesized by the following steps:
[0009] 1) dissolving high molecular weight polyvinyl pyrrolidone, trisodium citrate and soluble divalent copper salt in a mixed solvent of polyethylene glycol and water, and stirring until completely dissolved;
[0010] 2) dropping a strong alkaline solution into the solution prepared in step 1), stirring vigorously and then quickly adding a reducing agent, and stopping after the reaction is complete under stirring;
[0011] 3) The reaction product is separated, washed and vacuum dried.
[0012] On the basis of the above scheme and as a preferred scheme of the above scheme: the number average molecular weight of the polyvinyl pyrrolidone in step 1) is between 100,000 and 2,000,000.
[0013] On the basis of the above scheme and as a preferred scheme of the above scheme: the amount of polyvinyl pyrrolidone used in step 1) is 5-20 grams per mole of copper.
[0014] On the basis of the above scheme and as a preferred scheme of the above scheme: the molecular weight of the polyethylene glycol described in step 1) is between 100-900.
[0015] On the basis of the above scheme and as a preferred scheme of the above scheme: the ratio of polyethylene glycol to water in step 1) is 1:4-1:0.25.
[0016] On the basis of the above scheme and as a preferred scheme of the above scheme: the strong alkaline solution described in step 2) is sodium hydroxide, potassium hydroxide or cesium hydroxide; the reducing agent described in step 2) is ascorbic acid, sodium ascorbate or hydrazine.
[0017] On the basis of the above scheme and as a preferred scheme of the above scheme: the reaction temperature of step 2) is 0-50°C; the separation method in step 3) is centrifugation or filtration.
[0018] On the basis of the above scheme and as a preferred scheme of the above scheme: the particle size of the cuprous oxide nanoparticles is between 100-300 nanometers; the crystal domain size of the cuprous oxide nanoparticles is less than 1 / 4 of the particle size.
[0019] On the basis of the above scheme and as a preferred scheme of the above scheme: the self-assembly of cuprous oxide nanoparticles is achieved by dipping, printing or spraying.
[0020] The invention discloses a fabric with rainbow colors. The cuprous oxide nanoparticle photonic crystal with rainbow colors and an adhesive are compounded and adhered to the surface of the fabric. The adhesive is polyacrylate, polyurethane or polyvinyl butyral.
[0021] The method for preparing iridescent cuprous oxide nanoparticle photonic crystals of the present invention has the following outstanding and beneficial technical effects compared with the prior art:
[0022] The invention adopts a mixed solvent of water and polyethylene glycol to synthesize cuprous oxide nanoparticles, and uses high molecular weight polyvinyl pyrrolidone to stabilize the generated nanoparticles. Due to its large molecular weight, polyethylene glycol can effectively inhibit the growth of cuprous oxide single crystals, and high molecular weight polyvinyl pyrrolidone is a weak flocculant, which can aggregate single crystal particles into larger particles.
[0023] The cuprous oxide nanoparticles prepared by the above method are spherical and can self-assemble and tightly stack into photonic crystals with a three-dimensional ordered structure, thus presenting brilliant iridescent colors. The use of adhesives greatly improves the fastness of the resulting structural color on the fabric surface, while the brilliance of the iridescent color is not reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 : Scanning electron micrographs of cuprous oxide nanoparticles at different molar ratios of sodium citrate to cupric acetate, and the relationship between average particle size, monodispersity index and molar ratio of sodium citrate to cupric acetate. Among them: (a) molar ratio of sodium citrate to cupric acetate 0.7:1; (b) molar ratio of sodium citrate to cupric acetate: 0.8:1; (c) molar ratio of sodium citrate to cupric acetate: 1:1; (d) molar ratio of sodium citrate to cupric acetate: 1.2:1; (e) molar ratio of sodium citrate to cupric acetate: 1.3:1.
[0025] Figure 2 : Relationship diagram of average particle size of cuprous oxide nanoparticles at different molar ratios of sodium citrate to cupric acetate;
[0026] Figure 3 : Transmission electron microscopy image of cuprous oxide nanoparticles with a particle size of 212 nm.
[0027] Figure 4 : Wide-angle X-ray diffraction pattern of cuprous oxide nanoparticles with a particle size of 212 nm.
[0028] Figure 5 : Scanning electron micrographs of cuprous oxide nanoparticles synthesized in (a) aqueous solution of ethylene glycol and (b) using lower molecular weight polyvinyl pyrrolidone.
[0029] Figure 6 : Polyester fabric dyed with photonic crystals constructed with cuprous oxide nanoparticles of different sizes.
[0030] Figure 7 : Color 3D microscope photos of photonic crystals constructed from cuprous oxide nanoparticles of different particle sizes and combined with adhesives on a textile substrate to construct photonic crystal structures.
[0031] Figure 8 : Comparison of cuprous oxide nanoparticle photonic crystals bonded with polyvinyl butyral before and after washing. DETAILED DESCRIPTION
[0032] The present invention is further described below with reference to specific embodiments in conjunction with the accompanying drawings. In the following embodiments, unless otherwise specified, the reagents, materials and equipment used can be purchased from commercial sources, or prepared by conventional methods, or commonly used in the industry. Unless otherwise specified, all percentages are in mass units.
[0033] A method for preparing iridescent cuprous oxide nanoparticle photonic crystals, wherein the structural unit is a polycrystalline monodisperse spherical cuprous oxide nanoparticle, which is synthesized by the following steps:
[0034] 1) dissolving high molecular weight polyvinyl pyrrolidone, trisodium citrate and soluble divalent copper salt in a mixed solvent of polyethylene glycol and water, and stirring until completely dissolved; the water-soluble divalent copper salt is copper acetate, copper chloride or copper sulfate, etc.;
[0035] 2) dropping a strong alkaline solution into the solution prepared in step 1), stirring vigorously and then quickly adding a reducing agent, reacting for a certain period of time under stirring until the reaction is complete, and then stopping;
[0036] 3) The reaction product is separated, washed and vacuum dried.
[0037] The polycrystalline monodispersed spherical cuprous oxide nanoparticles were obtained.
[0038] The number average molecular weight of the polyvinyl pyrrolidone in step 1 is between 100,000 and 2,000,000, preferably between 200,000 and 1,500,000, and more preferably between 500,000 and 1,500,000.
[0039] The amount of polyvinyl pyrrolidone used in step 1) is 5-20 grams per mole of copper, preferably 10-15 grams. The molecular weight of the polyethylene glycol in step 1) is between 100-900, preferably between 300-750. The ratio of the polyethylene glycol to water in step 1) is 1:4-1:0.25, preferably 1:2-1:0.5.
[0040] The strong alkaline solution in step 2) is sodium hydroxide, potassium hydroxide, cesium hydroxide, including but not limited to these. The reducing agent in step 2) is ascorbic acid, sodium ascorbate, hydrazine, including but not limited to these.
[0041] The reaction temperature of step 2) is 0-50°C, preferably 20-30°C.
[0042] The separation method described in step 3) is centrifugation or filtration, including but not limited to these.
[0043] The particle size of the cuprous oxide nanoparticles is between 100 and 300 nanometers; the crystal domain size of the cuprous oxide nanoparticles is less than 1 / 4 of the particle size;
[0044] The diameter of cuprous oxide nanoparticles can be mainly controlled by the amount of trisodium citrate used. The particle size increases with the increase of the molar ratio of trisodium citrate to copper ions ( Figure 1 ).
[0045] The self-assembly of cuprous oxide nanoparticles can be achieved by commonly used methods, such as dipping, printing or spraying, including but not limited to these.
[0046] The photonic crystals formed by the self-assembly of cuprous oxide nanoparticles can be compounded with an adhesive to improve their fastness on the fabric surface. The adhesive can be polyacrylate, polyurethane, polyvinyl butyral, etc., including but not limited to these.
[0047] The cuprous oxide nanoparticles prepared by the above method can be densely stacked into photonic crystals with a three-dimensional ordered structure through self-assembly, thereby obtaining brilliant iridescent colors. The use of an adhesive greatly improves the fastness of the obtained structural color on the surface of the fabric, while the brilliant degree of the iridescent color is basically not reduced.
[0048] Black polyester fabric was used as the textile substrate to examine the color-producing effect of cuprous oxide nanoparticle photonic crystals.
[0049] Before self-assembly, the polyester fabric was hydrophilized by plasma treatment as follows: first, the polyester fabric was ultrasonically cleaned and cut into suitable sizes. A water-repellent treatment solution was prepared and impregnated into the fabric for 30 minutes. The fabric was rolled dry using a horizontal rolling mill, then dried at 90°C, and finally baked at 160°C for 3 minutes to ensure that both sides of the fabric were hydrophobic.
[0050] After the hydrophobic fabric is ironed with an electric iron, the fabric is treated with a cold plasma modification device with a power of 30-120w, a duration of 20-100s, and a vacuum degree of 30Pa.
[0051] The spraying method is adopted: the pressure applied by the compressor is set to 0.5PSI, and the diameter of the spray gun is 0.2mm; the spraying process is: spraying time 10s, spraying distance 10cm.
[0052] The photonic crystal structure color textiles using adhesives were ultrasonically washed to evaluate the stability of the photonic crystal color-producing structure. Specifically, an ultrasonic oscillator was selected to carry out a washing test on the photonic crystal structure color textiles, with an ultrasonic frequency of 120KHZ, an ultrasonic power of 120W, and an ultrasonic time of 10min.
[0053] Embodiment 1:
[0054] 50 g of polyethylene glycol with a number average molecular weight of 750 was dissolved in 250 mL of deionized water to obtain an aqueous solution of polyethylene glycol.
[0055] 2.00 g of polyvinyl pyrrolidone with a number average molecular weight of 250,000, 0.30 of copper acetate monohydrate (1.5 mmol) and different amounts of trisodium citrate dihydrate (1.05, 1.2, 1.5, 1.8, 1.95 mmol) were weighed in a beaker, and these compounds were dissolved in an aqueous solution of polyethylene glycol under the action of a magnetic stirrer.
[0056] 0.32 g of ascorbic acid was dissolved in 15 mL of deionized water to prepare a reducing agent solution.
[0057] Under 25°C water bath conditions, 20 mL of 0.5 M sodium hydroxide solution was rapidly dripped into the obtained copper oxide precursor solution under vigorous stirring, and 15 mL of 2% ascorbic acid aqueous solution was added after stirring for 10 minutes. The reaction was stopped after 60 minutes of stirring, and the reaction product was obtained by centrifugation at a speed of 5000 r / min for 5 minutes, and washed three times with a mixture of water and ethanol to remove excess ligands, and vacuum dried for use.
[0058] SEM images of cuprous oxide nanoparticles ( Figure 1) showed that the obtained particles have good monodispersity (dispersion index PDI≤0.08) and can self-assemble into a three-dimensional ordered photonic crystal structure.
[0059] Through transmission electron microscopy ( Figure 3 ) Research has shown that the particles synthesized by this method are spherical and have a polycrystalline structure.
[0060] Figure 4 The wide-angle X-ray diffraction pattern of these particles is analyzed by the Scherrer formula, and the crystal domain size D is obtained to be 21 nanometers, which is 1 / 10 of the particle size.
[0061] D=Kλ / (βcosθ)
[0062] Where K is a constant; λ is the wavelength of X-rays; β is the half-width of the diffraction peak; θ is the diffraction angle.
[0063] Embodiment 2:
[0064] Dissolve 50 g of ethylene glycol in 250 mL of deionized water to obtain an ethylene glycol aqueous solution which is different from the polyethylene glycol in Example 1.
[0065] 2.00 g of polyvinyl pyrrolidone having a number average molecular weight of 250,000, 0.30 of copper acetate monohydrate (1.5 mmol) and 0.51 g of trisodium citrate dihydrate (1.8 mmol) were weighed in a beaker and dissolved in an aqueous solution of ethylene glycol under the action of a magnetic stirrer.
[0066] 0.32 g of ascorbic acid was dissolved in 15 mL of deionized water to prepare a reducing agent solution.
[0067] Under 25°C water bath conditions, 20 mL of 0.5 M sodium hydroxide solution was rapidly dripped into the obtained copper oxide precursor solution under vigorous stirring, and 15 mL of 2% ascorbic acid aqueous solution was added after stirring for 10 minutes. The reaction was stopped after 60 minutes of stirring, and the reaction product was obtained by centrifugation at a speed of 5000 r / min for 5 minutes, and washed three times with a mixture of water and ethanol to remove excess ligands, and vacuum dried for use.
[0068] SEM images of the obtained cuprous oxide nanoparticles ( Figure 5 a) shows that the obtained particles are not spherical, so they cannot self-assemble into a three-dimensional ordered photonic crystal structure. Analysis of the wide-angle X-ray diffraction patterns of these particles using the Scherrer formula shows that the crystal domain size is similar to the particle size, indicating that these particles are single crystals.
[0069] Embodiment 3:
[0070] 50 g of polyethylene glycol with a number average molecular weight of 500 was dissolved in 250 mL of deionized water to obtain an aqueous solution of polyethylene glycol.
[0071] 2.00 g of polyvinyl pyrrolidone with a number average molecular weight of 56,000, 0.30 g of copper acetate monohydrate (1.5 mmol) and 0.51 g of trisodium citrate dihydrate (1.8 mmol) were weighed in a beaker and dissolved in an aqueous solution of ethylene glycol under the action of a magnetic stirrer. 0.32 g of ascorbic acid was dissolved in 15 mL of deionized water to prepare a reducing agent solution.
[0072] Under 25°C water bath conditions, 20 mL of 0.5 M sodium hydroxide solution was rapidly dripped into the obtained copper oxide precursor solution under vigorous stirring, and 15 mL of 2% ascorbic acid aqueous solution was added after stirring for 10 minutes. The reaction was stopped after 60 minutes of stirring, and the reaction product was obtained by centrifugation at a speed of 5000 r / min for 5 minutes, and washed three times with a mixture of water and ethanol to remove excess ligands, and vacuum dried for use.
[0073] SEM images of the obtained cuprous oxide nanoparticles ( Figure 5 b) shows that the obtained particles are not spherical, so they cannot self-assemble into a three-dimensional ordered photonic crystal structure. Analysis of the wide-angle X-ray diffraction patterns of these particles using the Scherrer formula shows that the crystal domain size is similar to the particle size, indicating that these particles are single crystals.
[0074] Table 1
[0075]
[0076] The present invention innovatively replaces the monomer ethylene glycol with polyethylene glycol, and adds high molecular weight polyvinyl pyrrolidone as a weak flocculant, thereby obtaining spherical cuprous oxide nanoparticles with a polycrystalline structure and achieving washable structural colors with an iridescent effect on textiles.
[0077] Due to its large molecular weight, polyethylene glycol can effectively inhibit the growth of cuprous oxide single crystals, while high molecular weight polyvinyl pyrrolidone is a weak flocculant that can aggregate single crystal particles into larger particles.
[0078] Dyeing fabric: Example 4
[0079] At room temperature, 2% (in terms of solid content) of cuprous oxide nanoparticles with different particle sizes were dispersed in anhydrous alcohol by ultrasound, and then the dispersion was added to the spray gun system and sprayed on the polyester fabric. The sprayed textile was placed in an oven at 160°C for 1 minute to dry, and a photonic crystal color-forming structure with dense and orderly particle arrangement was obtained. The fabric showed obvious iridescence ( Figure 6 ).
[0080] Photonic crystal bonding adhesive: Example 5
[0081] At room temperature, 4% (in terms of solid content) of cuprous oxide nanoparticles with a particle size of 205nm and a dispersion index (PDI) of 0.07 and 2.5% of the binder polyvinyl butyral were dispersed in anhydrous alcohol, and then ultrasonically treated for 15 minutes to obtain a structural color-forming spray liquid. The spray liquid was sprayed on polyester fabric, and the sprayed textile was placed in a 160°C oven for 1 minute to dry, and a blue photonic crystal color-forming structure ( Figure 7 a1). After ultrasonic washing, the structural color of the structural color-producing textiles did not diminish, and the photonic crystal structure did not fall off at all ( Figure 8 ).
[0082] Photonic crystal bonding adhesive: Example 6
[0083] At room temperature, 5% (in terms of solid content) of cuprous oxide nanoparticles with a particle size of 223nm and a dispersion index (PDI) of 0.03 and 3% of the binder polyvinyl butyral were dispersed in anhydrous alcohol, and then ultrasonically treated for 15 minutes to obtain a structural color-forming spray liquid. The spray liquid was sprayed on polyester fabric, and the sprayed textile was placed in an oven at 160°C for 1 minute to dry, and a green photonic crystal color-forming structure ( Figure 7 a2). After ultrasonic washing, the structural color of the structural color-producing textiles did not diminish and the photonic crystal structure did not fall off.
[0084] Photonic crystal bonding adhesive: Example 7
[0085] At room temperature, 2% (in terms of solid content) of cuprous oxide nanoparticles with a particle size of 274nm and a dispersion index (PDI) of 0.04 and 3% of the binder polyvinyl butyral were dispersed in anhydrous alcohol, and then ultrasonically treated for 15 minutes to obtain a structural color-forming spray liquid. The spray liquid was sprayed on polyester fabric, and the sprayed textile was placed in a 160°C oven for 1 minute to dry, obtaining a red photonic crystal color-forming structure ( Figure 7 a3). After ultrasonic washing, the structural color of the structural color-producing textiles did not diminish and the photonic crystal structure did not fall off.
[0086] The above embodiments are only preferred embodiments of the present invention and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing iridescent cuprous oxide nanoparticle photonic crystals, characterized in that: The structural unit is a polycrystalline monodisperse spherical cuprous oxide nanoparticle, which is synthesized by the following steps: 1) dissolving high molecular weight polyvinyl pyrrolidone, trisodium citrate and soluble divalent copper salt in a mixed solvent of polyethylene glycol and water, and stirring until completely dissolved; 2) dropping a strong alkaline solution into the solution prepared in step 1), stirring vigorously and then quickly adding a reducing agent, and stopping after the reaction is complete under stirring; 3) The reaction product is separated, washed and vacuum dried.
2. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The number average molecular weight of the polyvinyl pyrrolidone in step 1) is between 100,000 and 2,000,000.
3. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The amount of polyvinyl pyrrolidone used in step 1) is 5-20 grams per mole of copper.
4. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The molecular weight of the polyethylene glycol in step 1) is between 100-900.
5. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The ratio of the polyethylene glycol to water in step 1) is 1:4-1:0.
25.
6. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The strong alkaline solution in step 2) is sodium hydroxide, potassium hydroxide or cesium hydroxide; the reducing agent in step 2) is ascorbic acid, sodium ascorbate or hydrazine.
7. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The reaction temperature of step 2) is 0-50°C; the separation method of step 3) is centrifugation or filtration.
8. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The particle size of the cuprous oxide nanoparticles is between 100 and 300 nanometers; the crystal domain size of the cuprous oxide nanoparticles is less than 1 / 4 of the particle size.
9. The method for preparing iridescent cuprous oxide nanoparticle photonic crystals according to claim 1, characterized in that: The self-assembly of cuprous oxide nanoparticles is achieved by dipping, printing or spraying.
10. A fabric having rainbow colors, characterized in that: The iridescent cuprous oxide nanoparticle photonic crystals according to any one of claims 1 to 9 are compounded with an adhesive and pasted on the surface of fabric; the adhesive is polyacrylate, polyurethane or polyvinyl butyral.
Citation Information
Patent Citations
A monodisperse Cu₂O single-crystal solid sphere with adjustable particle size and its preparation method
CN109850932B
Spherical cuprous oxide micro-nano particles with roughness surface and preparation method thereof
CN103435089A
Preparation method of graded spherical cuprous oxide hollow nano particle
CN103466681A
Method for producing cuprous oxide particle and cuprous oxide particle
JP2006096655A
Cited By
Multifunctional structural color antibacterial fabric based on CuO nanospheres and preparation method thereof
CN120556276A
Preparation method of cuprous oxide quantum dots
CN120589778A